2018
DOI: 10.1037/vio0000088
|View full text |Cite
|
Sign up to set email alerts
|

Antisocial traits, distress tolerance, and alcohol problems as predictors of intimate partner violence in men arrested for domestic violence.

Abstract: These results support and extend existing conceptual models of IPV perpetration. Findings suggest intervention efforts for IPV should target both distress tolerance and alcohol problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 53 publications
(90 reference statements)
2
36
0
2
Order By: Relevance
“…Different personality traits and disorders also represent possible risk factors of IPV perpetration (Capaldi et al, 2012). In particular, antisocial personality traits and antisocial personality disorder (APD) have been broadly studied in relation with male-to-female IPV perpetration (Brem, Florimbio, Elmquist, Shorey, & Stuart, 2018;Capaldi et al, 2012;. Batterer typologies, for example, have identified specific types of batterers characterized by a large criminal curriculum, violence within and outside the family, including batterers that are: dominating and violent/bully (Faulk, 1974), controllers (Elbow, 1977), tyrants (Caesar, 1986), undercontrolled with regard to hostility (Hershorn & Rosenbaum, 1991), narcissistic/antisocial (Hamberger & Hastings, 1986), antisocial and sociopathic (Gondolf, 1988), generally violent (Herrero, Torres, Fernández-Suárez, & Rodríguez-Díaz, 2016;Saunders, 1992), and generally violent/antisocial (Holtzworth-Munroe & Stuart, 1994).…”
Section: Individual Characteristics and Ipv: Antisocial Personality Tmentioning
confidence: 99%
“…Different personality traits and disorders also represent possible risk factors of IPV perpetration (Capaldi et al, 2012). In particular, antisocial personality traits and antisocial personality disorder (APD) have been broadly studied in relation with male-to-female IPV perpetration (Brem, Florimbio, Elmquist, Shorey, & Stuart, 2018;Capaldi et al, 2012;. Batterer typologies, for example, have identified specific types of batterers characterized by a large criminal curriculum, violence within and outside the family, including batterers that are: dominating and violent/bully (Faulk, 1974), controllers (Elbow, 1977), tyrants (Caesar, 1986), undercontrolled with regard to hostility (Hershorn & Rosenbaum, 1991), narcissistic/antisocial (Hamberger & Hastings, 1986), antisocial and sociopathic (Gondolf, 1988), generally violent (Herrero, Torres, Fernández-Suárez, & Rodríguez-Díaz, 2016;Saunders, 1992), and generally violent/antisocial (Holtzworth-Munroe & Stuart, 1994).…”
Section: Individual Characteristics and Ipv: Antisocial Personality Tmentioning
confidence: 99%
“…The individual level represents the personal history of the partner or the woman (Pinnewala, 2009). A partner’s personal history of witnessing marital violence as a child, experiencing child abuse, having a personality disorder, and problem with alcohol use have been identified as risk factors for IPV in prior research (Brem, Florimbio, Elmquist, Shorey, & Stuart, 2018; Heise, 1998; Pinnewala, 2009). Women married at a younger age with little education and low socioeconomic status are likely to adhere to norms justifying IPV (Jesmin, 2015), which places them at risk for exposure to IPV.…”
mentioning
confidence: 99%
“…Authors of a recent validation study on a domestic abuse risk assessment tool in the U.K. (Domestic Abuse, Stalking and harassment and Honour-based violence; DASH) also reported that problematic alcohol use was significantly positively related to repeat general and violent domestic abuse (note that offenders' gender was not specified; Almond, McManus, Brian, & Merrington, 2017). Substance abuse has further been identified as a significant predictor of male-and female-perpetrated IPV onset and recidivism in various other studies (Brem et al, 2018;Fals-Stewart, 2003;Gordon & Moriarty, 2003;Murphy, Morrel, Elliott, & Neavins, 2003;Shepard, 1992;Tollefson & Gross, 2006;Whitaker, Le, & Niolon, 2010).…”
Section: Draor With Intimate Partner Violence Offendersmentioning
confidence: 98%
“…For instance, dynamic risk factors predict violence and serious misconducts-such as escape, smuggling, and inappropriate sexual behaviour-among incarcerated and hospitalized offenders (Hogan & Olver, 2016;Van Voorhis et al, 2010;Wilson, Desmarais, Nicholls, Hart, & Brink, 2013;Yang, Wong, & Coid, 2010). Dynamic risk factors also predict rearrest, reimprisonment, and/or hospital readmission for IPV, violent, nonviolent, and sex offences among community-supervised offenders (Brem, Florimbio, Elmquist, Shorey, & Stuart, 2018;Brown, et al, 2009;Feder & Dugan, 2002;Greiner, Law, & Brown, 2015;Hanby, 2013;Hilton & Harris, 2005;McCoy & Miller, 2013;Olver, Wong, Nicholaichuk, & Gordon, 2007;Penney, Marshall, & Simpson, 2016;Van Voorhis et al, 2010).…”
Section: Dynamic Risk Assessmentmentioning
confidence: 99%